GEN-27, a Newly Synthetic Isoflavonoid, Inhibits the Proliferation of Colon Cancer Cells in Inflammation Microenvironment by Suppressing NF-κB Pathway - Yajing Wang; Ping Lu; Weifeng Zhang; Qianming Du; Jingjing Tang; Hong Wang; Jinrong Lu; Rong Hu (Mediators of Inflammation)
Nonresolving inflammation is one of the consistent features of the tumor microenvironment in the intestine and plays a critical role in the initiation and development of colon cancer. Here we reported the inhibitory effects of GEN-27, a new derivative of genistein, on the inflammation-related colon cancer cell proliferation and delineated the mechanism of its action. The results indicated that GEN-27 inhibited the proliferation of human colon tumor HCT116 cells stimulated by culture supernatants of LPS-induced human monocytes THP-1 cells and significantly decreased LPS-induced secretion of proinflammatory cytokines interleukin-6 and interleukin-1β in THP-1 cells. The HCT116 cell proliferation elicited by THP-1-conditioned medium could be blocked by the interleukin-1 receptor antagonist (IL-1RA). Further mechanistic study revealed that GEN-27 remarkably inhibited the nuclear translocation of NF-κB and phosphorylation of IκB and IKKα/β in both HCT116 and THP-1 cells. In addition, GEN-27 markedly suppressed the HCT116 cell proliferation stimulated by IL-1β treatment, which was dependent on the inhibition of NF-κB/p65 nuclear localization, as verified by p65 overexpression and BAY 11-7082, an NF-κB inhibitor. Taken together, our findings established that GEN-27 modulated NF-κB signaling pathway involved in inflammation-induced cancer cells proliferation and therefore could be a potential chemopreventive agent against inflammation-associated colon cancer.